Factores de riesgo determinantes asociados a caries dental en niños de 6 a 12 años. Revisión de la literatura (2021)
Dental caries is the most widespread health problem among the population of all ages and although a clear decline has been observed in recent years in developed countries, the same does not happen in less wealthy countries, which has sparked interest of researchers to study the risk factors of dental caries, as well as its prevalence.